DNAm-based signatures of accelerated aging and mortality in blood are associated with low renal function - Matías-García, Pamela R.; Ward-Caviness, Cavin K.; Raffield, Laura M.; Gao, Xu; Zhang, Yan; Wilson, Rory; Gao, Xin; Nano, Jana; Bostom, Andrew; Colicino, Elena; Correa, Adolfo; Coull, Brent; et al. (Clinical epigenetics, 2021)
The difference between an individual's chronological and DNA methylation predicted age (DNAmAge), termed DNAmAge acceleration (DNAmAA), can capture life-long environmental exposures and age-related physiological changes reflected in methylation status. Several studies have linked DNAmAA to morbidity and mortality, yet its relationship with kidney function has not been assessed. We evaluated the associations between seven DNAm aging and lifespan predictors (as well as GrimAge components) and five kidney traits (estimated glomerular filtration rate [eGFR], urine albumin-to-creatinine ratio [uACR], serum urate, microalbuminuria and chronic kidney disease [CKD]) in up to 9688 European, African American and Hispanic/Latino individuals from seven population-based studies.